Detection of Rocky Mountain spotted fever antibodies by a latex agglutination test. - Hechemy, K E (1980)
A latex test for immunodiagnosis of Rocky Mountain spotted fever, using erythrocyte-sensitizing substance from Rickettsia rickettsii adsorbed to latex particles, has been developed. The test was evaluated with a total of 123 single and 118 paired human sera submitted for Rocky Mount spotted fever testing. This test is simple, sensitive, and specific. Its efficiency, relative to the reference microimmunofluorescence test, was 95.1% for single sera and approached 100% for paired sera.